Laws, Enforcement, Legality, and Economic Development - Frank H. Stephen; Stefan Van Hemmen (Washington University Journal of Law & Policy, 2008)
This Essay will examine the relationship between laws, enforcement, legality, and economic development by utilizing a framework developed within the New Institutional Economics.
Keywords: Law & amp; economics; Institutional economics; Economic development; New institutional economics (NIE); Governance; Institutional environment; United States